Purification of Xylooligosaccharide From Casavva Pulp by Ultrafiltration Method - Ratnadewi, Anak Agung Istri; Fauziyah, Kamelia Rizqi; Indarti, Dwi (Universitas Jember, 2021)
Xylan is the main component of hemicellulose. Xylan can be extracted from agricultural waste, such as cassava pulp. Xylan is used as an endo-β-1,4-D-xylanase substrate to produce impure xylooligosaccharides (XOS)This study aims to purify XOS from cassava pulp using the ultrafiltration method. The components of XOS obtained from the enzymatic hydrolysis were analyzed using thin layer chromatography (TLC) and densitometry methods. In addition, the XOS was purified by the ultrafiltration method using a cellulose membrane with a Molecular Weight Cut Off (MWCO) of 12 kDa. The permeate obtained from the purification results was also analyzed using TLC and densitometry. The results of this study indicated that the components in XOS cassava pulp before and after purification by the TLC method were X5 and X6, while the XOS components before and after purification by the densitometric method were X3, X4 and X5.